CAD for Robotics: Trends, Opportunities, Considerations, and Constraints - Andi Almeira Zocha Ismail; Andi Regina Acacia Ismail; Azmi Shawkat Abdulbaqi; Ismail Yusuf Panessai (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
In Southeast Asia, the integration of Computer-Aided Design (CAD) into robotics development has become increasingly vital in meeting the growing demand for rapid, task-specific automation. CAD plays a central role in enhancing how robotic systems are designed, simulated, and prototyped—enabling improved design precision, reduced development time, and accelerated innovation. This paper investigates the current trends in CAD applications for robotics and highlights key opportunities, including collaborative design approaches, rapid prototyping capabilities, and the convergence of digital engineering tools. Furthermore, the study discusses critical technical considerations such as software interoperability, real-time simulation integration, and the need for upskilling in CAD-related competencies. Drawing from both academic research and industrial practice across Southeast Asian countries, the findings reveal a pressing need for tighter integration between CAD platforms, robotic simulation environments, and control systems. The analysis identifies several regional challenges, including limited access to advanced CAD tools, inconsistent adoption in educational curricula, and disparities in technical training infrastructure. The paper concludes with strategic recommendations to support the growth of CAD-driven robotics in the region: bridging the digital skills gap, improving access to design technologies, promoting cross-institutional collaboration, and encouraging targeted research to adapt CAD tools to local industrial needs. These efforts are crucial for enabling Southeast Asia to capitalize on CAD’s transformative potential in developing agile, affordable, and application-specific robotic solutions.